2008
DOI: 10.3177/jnsv.54.501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Docosahexaenoic Acid Connecting Phospholipids on the Lipid Peroxidation of the Brain in Mice

Abstract: SummaryThe effect of dietary docosahexaenoic acid (DHA, C22:6 n -3) with two lipid types on lipid peroxidation of the brain was investigated in streptozotocin (STZ)-induced diabetic mice. Each group of female Balb/c mice was fed a diet containing DHA-connecting phospholipids (DHA-PL) or DHA-connecting triacylglycerols (DHA-TG) for 5 wk. Safflower oil was fed as the control. The lipid peroxide level of the brain was significantly lower in the mice fed the DHA-PL diet when compared to those fed the DHA-TG and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
2
27
1
Order By: Relevance
“…In the studies of rats or mice fed the TG and PL types of DHA diets, the DHA levels in the brain and liver of the DHA-TG diet group were significantly higher than those of the DHA-PL diet group (31,32). However, in the present study and our previous study (7), in which diabetes was induced in mice using streptozotocin, there were no significant differences in the DHA levels of the brains between the DHA-TG and DHA-PL diet groups. It is considered that several factors, such as the ratio of n-3/n-6 and the exact intake of DHA, affect DHA level of each organ when an experiment using dietary DHA is carried out.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In the studies of rats or mice fed the TG and PL types of DHA diets, the DHA levels in the brain and liver of the DHA-TG diet group were significantly higher than those of the DHA-PL diet group (31,32). However, in the present study and our previous study (7), in which diabetes was induced in mice using streptozotocin, there were no significant differences in the DHA levels of the brains between the DHA-TG and DHA-PL diet groups. It is considered that several factors, such as the ratio of n-3/n-6 and the exact intake of DHA, affect DHA level of each organ when an experiment using dietary DHA is carried out.…”
Section: Discussioncontrasting
confidence: 53%
“…In our previous study ( 7 ), which compared the effects of the PL and TG types of dietary DHA on the lipid peroxidation of the brain in STZ-induced diabetic mice, the DHA-PL diet group showed antioxidant activity in the brain lipid, and the plasmalogen level of the brain was higher than that of the DHA-TG group. Therefore, we suggested that the effect of the antioxidant activity of the brain lipid was related to the plasmalogen concentration.…”
mentioning
confidence: 99%
“…We showed that DHA administration increased plasma SOD like activity and suppressed the liver fi brosis, although plasma ALT and AST levels in NASH DHA group were still high. These fi nding supports that DHA develops an antioxidative role in vivo, although DHA is easily peroxidized 16 . As we previously reported 2, 4 , our model caused the increment of oxidative stress during NASH development.…”
Section: Discussionmentioning
confidence: 63%
“…The n-3 PUFA-enriched PLs used in existing studies were mainly obtained from krill or fish roe; the PLs contained 7-28 DHA and 5-12.5 EPA 26 33 . Supplementation with n-3 PUFAs in the form of PLs could improve the biological and nutritional benefits 24,25 , including anti-inflammatory actions 26,27 , antioxidant activity on brain lipids 10 , improved memory and learning 12 , reduced blood and tissue lipids 28 31 , increased bioavailability of EPA and DHA in plasma 32,33 , and a tendency toward reduced obesity 27,31 . The results can perhaps be ascribed to the amphiphilic character of phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested the PL form of DHA has anti-inflammatory and anti-oxidative functions 10 . Shirouchi B 11 reported that dietary PL increased serum adiponectin levels and prevented the development of nonalcoholic fatty liver disease in a rat model of metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%